pengaruh produksi cpo, harga internasional cpo, dan nilai tukar terhadap volume ekspor cpo (crude palm oil) indonesia (studi tahun 2001-2020) - Akbar, Muhamad; Dahlan, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to analize the effect of the production, International Price and Exchange Rate against the Export Volume of CPO in Indonesia in the 2001-2020 periods. The data used is secondary data obtained from the Central Statistics Agency, Bank Indonesia, Ministry of Agriculture, and web investing.com. This study uses time series data analysis with Multiple Linear Regression method. The result show that the Production, International Price and Exchange Rate have a positive and significant effect on the Export Volume of CPO in Indonesia in the 2001-2020.